1989
DOI: 10.1007/bf00199559
|View full text |Cite
|
Sign up to set email alerts
|

Dehydroxylation induced structural transformations in montmorillonite: an isothermal FTIR study

Abstract: Abstract. Fourier transform infrared (FTIR) measurementson thermally shocked (290< T< 1100 K, t= 1 and 24 h) and thermally soaked (T= 803 K, 0< t < 25 h) Ca-montmorillonite from Texas show that the dehydroxylation temperature for this mineral is much lower than previously reported in the literature and depends upon the thermal soak time used. The effect of thermal shock temperature on vibrational frequencies, originating from the silicate sheet, and the intensity of A1-OH-A1 stretching mode suggest that Camont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…3a. It shows the typical absorption bands of montmorillonite (Farmer, 1974), for example Al-OH-Al (Ogloza and Malhotra, 1989) stretching at 3625 cm −1 , OH (Ogloza and Malhotra, 1989;Russell, 1965) stretching of water at 3434 cm −1 and Si-O (Ogloza and Malhotra, 1989;Russell, 1965) bending at 1059 cm −1 . However, there is a broad peak at the band position of about 3220 cm −1 in Figs.…”
Section: Fourier Transform Infrared (Ft-ir) Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…3a. It shows the typical absorption bands of montmorillonite (Farmer, 1974), for example Al-OH-Al (Ogloza and Malhotra, 1989) stretching at 3625 cm −1 , OH (Ogloza and Malhotra, 1989;Russell, 1965) stretching of water at 3434 cm −1 and Si-O (Ogloza and Malhotra, 1989;Russell, 1965) bending at 1059 cm −1 . However, there is a broad peak at the band position of about 3220 cm −1 in Figs.…”
Section: Fourier Transform Infrared (Ft-ir) Analysismentioning
confidence: 99%
“…Ogloza and Malhotra, 1989) was conducted using a Bruker FT-IR spectrometer (Model Vector 22). About 1.0 mg mineral dust and 100 mg KBr were weighted and ground in an agate mortar prior to pellet making under a load of 1.0×10 4 kg of pressure for 2 min.…”
Section: Aerosol Surface Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Kok, 2008;Ledesma, Kalish, Nelson, Wornat, & Mackie, 2000;Liotta, Brons, & Isaacs, 1983;MacPhee, Giroux, Charland, Gransden, & Price, 2004;Mahidin, Usui, Ishikawa, & Hamdani, 2002;Ogloza & Malhotra, 1989;Painter, Snyder, Pearson, & Kwong, 1980;Rhoads, Senftle, Coleman, Davis, & Painter, 1983;Wu, Robbins, Winschel, & Burke, 1988). The changes of IR/FTIR spectra observed for a coal i.e.…”
Section: Ir/ftir Spectroscopymentioning
confidence: 99%
“…They found that the presence of ammonia gas decreased the ice nucleation ability of silver iodide particles. The interactions of the trace gases with mineral dust particles have been studied (Russell 1965;Ogloza and Malhotra 1989;Umann et al 2005). However, the potential impact of trace gases on ice nucleation is still not well understood.…”
Section: Introductionmentioning
confidence: 99%